2009
DOI: 10.1007/s00253-008-1766-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel highly acidic β-mannanase from the acidophilic fungus Bispora sp. MEY-1: gene cloning and overexpression in Pichia pastoris

Abstract: Using degenerate polymerase chain reaction (PCR) and thermal asymmetric interlaced PCR, a 1,347-bp full-length complementary DNA fragment encompassing the gene man5A, which encodes a 429-amino acid beta-mannanase with a calculated mass of 46.8 kDa, was cloned from acidophilic Bispora sp. MEY-1. The deduced amino acid sequence (catalytic domain) displayed highest identity (54.1%) with the Emericella nidulans endo-beta-1,4-D-mannanase, a member of the glycoside hydrolase family 5. Recombinant MAN5A was overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 21 publications
2
83
0
1
Order By: Relevance
“…are anamorphic fungi of Teratosphaeriaceae and that T. acidotherma forms a sister clade of these anamorphic fungi. Bispora and Acidomyces strains are similar to the present fungus in having acidophilic properties (Sigler and Carmichael 1974;Baker et al 2004;Luo et al 2008;Selbmann et al 2008). We found that the Bispora sp.…”
Section: Phylogenymentioning
confidence: 74%
See 3 more Smart Citations
“…are anamorphic fungi of Teratosphaeriaceae and that T. acidotherma forms a sister clade of these anamorphic fungi. Bispora and Acidomyces strains are similar to the present fungus in having acidophilic properties (Sigler and Carmichael 1974;Baker et al 2004;Luo et al 2008;Selbmann et al 2008). We found that the Bispora sp.…”
Section: Phylogenymentioning
confidence: 74%
“…Bispora sp. MEY-1 was isolated from acidic waste water of the ''721'' uranium mine in China, and its optimum pH for growth was reported as pH 2.5-3 (Luo et al 2008). Bispora sp.…”
Section: Phylogenymentioning
confidence: 99%
See 2 more Smart Citations
“…In general, extremozymes have attracted a great deal of interest due to their potential for practical applications. However, studies on fungal acidic enzymes still remain limited with a few exceptions including mannanase, xylanase (Luo et al 2009a(Luo et al , 2009b, and polygalacturonase (Yang et al 2011) from the acidophilic Bispora sp. strain MEY-1, or laccase from H. acidophila (Tetsch et al 2005).…”
Section: Fungi From Polluted Environments: a Rich Source For Bioexplomentioning
confidence: 99%